Cholestatic HCV-related cryoglobulinemia: A new clinical and pathological entity. (March 2023) - Dalbeni, A.; Romeo, S.; Amendola, S.; Cattazzo, F.; Tomezzoli, A.; Sacerdoti, D.
Abstract : Introduction and Aim: Mixed cryoglobulinemia (MC), the most common extrahepatic manifestation in chronic hepatitis C (CHC), can persist even after virus eradication, and it is a risk factor for development of cirrhosis. Up today, the relationship between MC and liver pathophysiology remains controversial, especially regarding intrahepatic cholestasis. This study aims to investigate the correlation between MC and intrahepatic cholestasis in CHC patients. Methods: 32 not yet eradicated HCV+ MC+ patients were enrolled, matched for age, sex and HCV genotype with 31 HCV+ MC-. For each participant, cholestatic parameters (direct bilirubin, alkaline phosphatase and gamma-glutamyl transferase), HCV-RNA, HCV genotype, plasma MC were measured; liver histology and plasma cells (aggregation and distribution), observed blinded by two operators, were analyzed. Patients with known autoimmune diseases were excluded from the study. Results were evaluated by the Mann-Whitney U or the Chi-squared tests and by stepwise multivariate analysis (p < 0.05). Results: 63 participants (mean age 57.1±11.1 years; males=50.8%) with CHC were enrolled. Serum cholestasis (2 or more increased cholestatic parameters) was significantly higher in MC+ group (p=0.025) and correlated in univariate analysis with cryoglobulinemia (OR 4.05; p=0.031). Plasma cells on liver histology were found in a significantly higher number in MC+ group (p=0.004) and tended to form aggregates more than in the control group (p=0.024). In stepwise multivariate analysis with genotype, HCV-RNA, steatosis, gender and age, cholestasis was only related to MC+ (OR 5.76; p=0.024). Conclusions: Our study identified for the first time a correlation between MC, cholestasis and intrahepatic plasma cells in patients with CHC before virus eradication. Future studies are needed to understand how MC causes cholestasis.